Determining factors that motivate people to live in gated communities / Afzan Natasha Suhana Md Izaninulhadi and Mohd Zaki Arif - Md Izaninulhadi, Afzan Natasha Suhana; Arif, Mohd Zaki (2018)
A gated community is a residential area which is surrounded by walls and fences. People live in gated communities because they believe that gated communities are safer places. However, several studies have been conducted which show that there are no differences between gated and non-gated residential areas but despite this, the trend of people living inside gated communities is increasing. Therefore, the purpose of this research is to identify the factors that motivate people to live inside gated communities; and then rank these factors. The method used in this research is quantitative technique. Based on the literature review, there are 8 factors that motivate people to live in gated communities. However after analysis was done using Exploratory Factor Analysis, only 4 factors were identified to be the the factors that motivate people to live in gated communities in Ipoh. These factors are prestige, location, property value and security. Prestige (2.3246) was ranked as the first factor followed by location (1.9474), property value (1.7982) and security (1.3480).